Novye podckody k razvitiju lovkosti bokserov - Kolesnik, I. S.; Nazarenko, L. D. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
In the research the authors started with the hypothesis, that the perfection of dexterity at boxers on its basic versions and displays will allow to increase the productivity of their competitive activity. To check the validity of the put forward hypothesis the pedagogical experiment was carried out. Two groups(14 persons each) of young boxers of 1-st category in the age of 16-17 years participated in it.